POSSIBLE SETTLEMENT OF PROPOSITION 65 ""DUKE II"" LITIGATION -- AFL-CIO, ET AL. V. DEUKMEJIAN, ET AL (Tufts Archival Research Center, 2007)
Memo regarding the possible settlement of a piece of litigation called Duke II, which would allow certain FDA regulated products to be exempt from warning labels for carcinogens until the state can officially define what constitutes a toxic substance. Asks recipients to look at the attached list of chemicals and to decide for which substances they would like the state to determine a "no significant risk level".